Proposal to create a Technological Career in Forensic Medicine to optimize justice in Ecuador - Balcázar-Ordóñez, Francisco (Universidad y Salud, 2025)
Introduction: Forensic medicine has evolved significantly in Ecuador since the creation of the Institute of Criminology in 1936 and the establishment of the National Service of Legal Medicine and Forensic Sciences in 2015. In a context of increasing violence, it is essential to strengthen technical training in this field. Objective: To analyze the feasibility of implementing a technological degree in Forensic Medicine in Ecuador, with emphasis on improving evidence management and providing comprehensive care to victims of violent acts. Materials and methods: A mixed-method, cross-sectional observational study was conducted using quantitative instruments (structured surveys) and qualitative instruments (content analysis) applied to high school students from four educational institutions in the city of Tena (Ecuador). Results: A high level of interest and acceptance toward the academic proposal was evidenced, highlighting the need to strengthen technical and professional competencies in the forensic field, despite certain methodological limitations such as unequal access to technology. Conclusion: The creation of this program will contribute to improving the administration of justice, optimizing the chain of custody, and ensuring more specialized care for victims.